Inhibition of glycosphingolipid biosynthesis reverts multidrug resistance by differentially modulating ABC transporters in chronic myeloid leukemias - Salustiano, Eduardo J. (J Biol Chem, 2020)
Multidrug resistance (MDR) in cancer arises from cross-resistance to structurally- and functionally-divergent chemotherapeutic drugs. In particular, MDR is characterized by increased expression and activity of ATP-binding cassette (ABC) superfamily transporters. Sphingolipids are substrates of ABC proteins in cell signaling, membrane biosynthesis, and inflammation, for example, and their products can favor cancer progression. Glucosylceramide (GlcCer) is a ubiquitous glycosphingolipid (GSL) generated by glucosylceramide synthase, a key regulatory enzyme encoded by the UDP-glucose ceramide glucosyltransferase (UGCG) gene. Stressed cells increase de novo biosynthesis of ceramides, which return to sub-toxic levels after UGCG mediates incorporation into GlcCer. Given that cancer cells seem to mobilize UGCG and have increased GSL content for ceramide clearance, which ultimately contributes to chemotherapy failure, here we investigated how inhibition of GSL biosynthesis affects the MDR phenotype of chronic myeloid leukemias. We found that MDR is associated with higher UGCG expression and with a complex GSL profile. UGCG inhibition with the ceramide analog d-threo-1-(3,4,-ethylenedioxy)phenyl-2-palmitoylamino-3-pyrrolidino-1-propanol (EtDO-P4) greatly reduced GSL and monosialotetrahexosylganglioside levels, and co-treatment with standard chemotherapeutics sensitized cells to mitochondrial membrane potential loss and apoptosis. ABC subfamily B member 1 (ABCB1) expression was reduced, and ABCC-mediated efflux activity was modulated by competition with nonglycosylated ceramides. Consistently, inhibition of ABCC-mediated transport reduced the efflux of exogenous C(6)-ceramide. Overall, UGCG inhibition impaired the malignant glycophenotype of MDR leukemias, which typically overcomes drug resistance through distinct mechanisms. This work sheds light on the involvement of GSL in chemotherapy failure, and its findings suggest that targeted GSL modulation could help manage MDR leukemias.